INFORMATION WARFARE AND METHODS OF POLITICAL MANIPULATION - Kuyliyev, B.T. (Oriental Journal of History, Politics and Law, 2025)
The article analyzes modern political technologies used to shape and influence public opinion through information warfare in the global information space. It explores the historical roots of the concept of information warfare, its main principles and methods, as well as manipulative strategies implemented via digital platforms and mass media. The paper also examines the impact of phenomena such as cyber propaganda, disinformation, and fake news on public consciousness, and discusses methods of their detection. The study is aimed at analyzing the influence of contemporary information wars on both national and global security.